A music-based HIV prevention intervention for urban adolescents. - Lemieux, Anthony F; Fisher, Jeffrey D; Pratto, Felicia (Health psychology : official journal of the Division of Health Psychology, American Psychological Association, 2008)
This research examines the process of conducting and evaluating a music-based HIV prevention intervention among urban adolescents, and is informed by the information, motivation, behavioral skills (IMB) model.
Keywords: Adolescent; Female; Health Promotion; HIV Infections; Humans; Male; Motivation; Music; Program Evaluation; Questionnaires; Safe Sex; Schools; Urban Population